2008
DOI: 10.1021/ja803082v
|View full text |Cite
|
Sign up to set email alerts
|

Selective Peptide Binding Using Facially Amphiphilic Dendrimers

Abstract: Amphiphilic dendrimers, which contain both hydrophobic and hydrophilic groups in every repeat unit, exhibit environment-dependent assemblies both in hydrophilic solvent, water, and in lipophilic solvent, toluene. Upon investigating the status of these assemblies in a mixture of immiscible solvents, these dendrimers were found to be kinetically trapped in the solvent in which they are initially assembled. This property has been exploited to selectively extract peptides from aqueous solution into an organic phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 71 publications
0
46
0
Order By: Relevance
“…We have previously reported that the most drastic change in the critical aggregation concentration (CAC) occurred from the monomer to G1-dendron; the CAC gain from the G1 to G2 dendron was relatively small. [4f,9,12] Therefore, we focused on the simpler G1 dendron for the studies outlined here. It is essential, however, that we confirm that the CAC for the G1 dendron 1 synthesized here is indeed in the micromolar range.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the most drastic change in the critical aggregation concentration (CAC) occurred from the monomer to G1-dendron; the CAC gain from the G1 to G2 dendron was relatively small. [4f,9,12] Therefore, we focused on the simpler G1 dendron for the studies outlined here. It is essential, however, that we confirm that the CAC for the G1 dendron 1 synthesized here is indeed in the micromolar range.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, these dendrimers are able to form micelle-type assemblies in an aqueous milieu and inverted micelle-type assemblies in apolar solvents, such as toluene. [12e,17] In contrast to classical amphiphilic dendrimers, [12a,d] the micellar assemblies from our dendrimers are formed through aggregation of several dendrimer molecules. This feature presents a unique opportunity for stimuli-induced disassembly in these dendrimers through disaggregation.…”
Section: Resultsmentioning
confidence: 99%
“…Dendrons of several generations containing a carboxyl moiety as the hydrophilic functionality and a decyl moiety as the hydrophobic functionality were synthesized and used to form inverse micelle type assemblies (Scheme 4) 62 with CACs of 50, 2.5, and 1 μM for G1, G2, and G3 dendrons, respectively.…”
Section: Supramolecular Assemblies For Peptide Extractionmentioning
confidence: 99%